2003
DOI: 10.1086/367677
|View full text |Cite
|
Sign up to set email alerts
|

Human Herpesvirus (HHV)–6 and HHV–7: Two Closely Related Viruses with Different Infection Profiles in Stem Cell Transplantation Recipients

Abstract: Human herpesvirus (HHV)-6 and HHV-7 loads were evaluated retrospectively in peripheral blood mononuclear cells (PBMC) from 78 recipients of stem cell transplantation (SCT) by real-time polymerase chain reaction. The median HHV-6 load in patients was 1357 genome equivalent copies (EqCop)/10(6) PBMC but was below the quantitation threshold in 31 immunocompetent individuals, which strongly suggests that HHV-6 reactivation occurred after SCT. The HHV-6 load was higher in patients with delayed neutrophil engraftmen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

9
81
4
5

Year Published

2004
2004
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 134 publications
(99 citation statements)
references
References 27 publications
9
81
4
5
Order By: Relevance
“…The reactivation of HHV-7 is observed before HHV-6 reactivation, which may suggest potential interaction between these viruses. These results are in accordance with those obtained in previous studies conducted in vitro (Katsafanas et al, 1996) and in vivo (Maeda et al, 2000;Boutolleau et al, 2003;Hall et al, 2006). However, Sassenscheidt et al (2006), Humar et al (2009), Tormo et al (2010 did not find evidence for potential interaction between HHV-6, HHV-7, and CMV.…”
Section: Discussionsupporting
confidence: 94%
See 1 more Smart Citation
“…The reactivation of HHV-7 is observed before HHV-6 reactivation, which may suggest potential interaction between these viruses. These results are in accordance with those obtained in previous studies conducted in vitro (Katsafanas et al, 1996) and in vivo (Maeda et al, 2000;Boutolleau et al, 2003;Hall et al, 2006). However, Sassenscheidt et al (2006), Humar et al (2009), Tormo et al (2010 did not find evidence for potential interaction between HHV-6, HHV-7, and CMV.…”
Section: Discussionsupporting
confidence: 94%
“…The ubiquitous nature of beta-herpesviruses creates conditions for the development of concurrent infection and interaction between these viruses. The kinetics of the activation of these viruses during the post-transplantation period suggests that HHV-7 can act as a co-factor for HHV-6 and CMV reactivation, while both -HHV-6 and HHV-7 can act as co-factors in CMV disease development (Miyoshi et al, 2001;Boutolleau et al, 2003). The prevalence of human herpesvirus reactivation ranges from 40 to 60% in auto-HSCT patients and usually occurs within 2-4 weeks (Zerr et al, 2005).…”
Section: Effect Of Hhv-6 and Hhv-7 Infection On The Post-transplant Pmentioning
confidence: 99%
“…22 Thus, we postulate that HHV6 originates from the reactivation of endogenous HHV6. Compared with MUD, in which the results were in the range of most reported studies, 22,24,25 CBT showed a significant by higher incidence and an higher median viral load of HHV6 infections and for a longer period of time after transplant. It was described earlier in three studies but with a short follow-up post transplant.…”
Section: Discussionmentioning
confidence: 60%
“…In our study, along with others, we have already reported the main consequence of HHV6 infection was to delay neutrophil and plt recoveries, especially in early reactivating patients. 25,27,37 Delayed engraftment is a well-known complication of cord blood transplant occurring at a higher incidence when compared with other source of SCs. [1][2][3][4]6 The role of HHV6 in delayed engraftment raises logically the question of HHV6 prophylaxis in CB transplant.…”
Section: Discussionmentioning
confidence: 99%
“…The length of the active infection (about 8 months) is the longest reported so far (1,5,8). Moreover, the viral load was constantly over 10 3 copies/10 5 PBMCs, which is regarded as the threshold value for an active viral replication and is considered a good marker for the onset of or association with relevant clinical disorders (1).…”
mentioning
confidence: 90%